Quantum Dots Do Not Alter the Differentiation Potential of Pancreatic Stem Cells and Are Distributed Randomly among Daughter Cells - S. Danner; H. Benzin; T. Vollbrandt; J. Oder; A. Richter; C. Kruse (International Journal of Cell Biology)
With the increasing relevance of cell-based therapies, there is a demand for cell-labeling techniques for in vitro and in vivo studies. For the reasonable tracking of transplanted stem cells in animal models, the usage of quantum dots (QDs) for sensitive cellular imaging has major advances. QDs could be delivered to the cytoplasm of the cells providing intense and stable fluorescence. Although QDs are emerging as favourable nanoparticles for bioimaging, substantial investigations are still required to consider their application for adult stem cells. Therefore, rat pancreatic stem cells (PSCs) were labeled with different concentrations of CdSe quantum dots (Qtracker 605 nanocrystals). The QD labeled PSCs showed normal proliferation and their usual spontaneous differentiation potential in vitro. The labeling of the cell population was concentration dependent, with increasing cell load from 5 nM QDs to 20 nM QDs. With time-lapse microscopy, we observed that the transmission of the QD particles during cell divisions was random, appearing as equal or unequal transmission to daughter cells. We report here that QDs offered an efficient and nontoxic way to label pancreatic stem cells without genetic modifications. In summary, QD nanocrystals are a promising tool for stem cell labeling and facilitate tracking of transplanted cells in animal models.